Women with a history of congenital anomaly: preparation for next pregnancy - Pribadi, Adhi (International Journal of Research in Medical Sciences, 2023)
Congenital diseases are damaging to the fetus and have an influence on the length of pregnancy. Some congenital problems can still be fixed after birth, however the costs are significant. Prophylaxis is strongly advocated to reduce the risk of congenital abnormalities during preconception. The incidence of congenital anomalies in the first pregnancy is associated with a 2.5-fold increased risk of recurrence in future pregnancies. The likelihood of recurrence is more than 24 times larger for the same type of aberration, but just 1.4 times for separate anomalies. The MTHFR-folate gene polymorphism has been related to an increased frequency of neural tube anomalies. Infectious diseases and environmental teratogens have an effect on genetic or epigenetic factors. Environmental elements that are repeated such maternal diabetes, obesity, and nutritional shortages seem to increase the incidence of fetal malformations. Alcohol, nicotine, or psychotropic drugs can all be teratogens. The promotion of contraceptive usage, optimization of weight and micronutrient status, prevention and management of infectious illnesses, birth spacing and the prevention of adolescent pregnancy, screening for and the management of chronic diseases are a few of these interventions. In conclusion, the probability of recurrence is quite high in the category of congenital defects, particularly for similar anomalies. Structural abnormalities can be decreased even further with proper planning and preparation, especially in high-risk populations. Moreover, preconception intervention have the potential to minimize congenital malformations.